2006
DOI: 10.1007/s10103-006-0406-x
|View full text |Cite
|
Sign up to set email alerts
|

A reasonable mechanism for visible light-induced skin rejuvenation

Abstract: In recent years, much research has been done in the field of non-ablative skin rejuvenation. This comes as a response to the continuous demand for a simple method of treating rhytides, UV exposure, and acne scars. Numerous researches involve visible light-pulsed systems (20-30 J/cm(2)). The mechanism of action is believed to be a selective heat-induced denaturalization of dermal collagen that leads to subsequent reactive synthesis (Bitter Jr., Dermatol. Surg., 26:836-843, 2000; Fitzpatrick et al., Arch. Dermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…This study confirms the clinical observation that low‐level exposure to 980 nm of diode laser light can accelerate cell growth in a wound‐healing model. Many studies have investigated the effects of visible red light on in vitro cell growth rates (2–4, 6, 19–23). Beyond the clinical setting, few experiments have studied the cellular progression of wound healing after exposure from light in the NIR spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirms the clinical observation that low‐level exposure to 980 nm of diode laser light can accelerate cell growth in a wound‐healing model. Many studies have investigated the effects of visible red light on in vitro cell growth rates (2–4, 6, 19–23). Beyond the clinical setting, few experiments have studied the cellular progression of wound healing after exposure from light in the NIR spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements suggested that IR exposure produced temperature increases <2 °C, and the use of a controlled incubation environment between image acquisition intervals further minimizes the temperature variability in our experiments. Previous researchers have suggested that light exposure increases ATP levels by altering the energetic state of light‐sensitive cytochromes within the inner mitochondrial membrane that participate in oxidative phosphorylation (19, 22, 23). Other research has demonstrated increased levels of cytokines (24) or growth factors (25) immediately following LLLT in similar in vitro models.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, a thermal effect where chromophores absorb the energy of the photons and convert this into heat, which subsequently diffuses throughout the skin or soft tissues. On the other hand, a nonthermal photochemical effect on the cells in the skin; photons are absorbed by cytochrome-c proteins, which are located on the membrane of the human dermal fibroblasts, resulting in an increased metabolic activity of the cells [7][8][9][10] As a consequence of a heat shock at a certain temperature and exposure time, skin can either be stimulated or damaged. 11 As a result, upregulation of the production of constructive proteins, (e.g., collagen, elastin, and proteoglycans) and heat shock proteins can be achieved.…”
Section: Biochemical and Thermal-mediated Eventsmentioning
confidence: 99%
“…A laser or another visible light device at the energy doses used for skin rejuvenation produces high amounts of reactive oxygen species, which destroy old collagen fibers and kill old skin cells, encouraging the formation of new ones. 21 Additionally, since it was known that these reactive oxygen species like O 2 Ã, OH*, and AsA* can increase skin cell damage, 22 it will be considered to allow efficient removal of skin cell or skin tissue by TP fiber laser irradiation. In other words, this result suggests that TP fiber laser device will be an effective technology to make more compact, low cost and less energy laser device for skin rejuvenation.…”
Section: Free Radical Generation By Tp Fiber Andmentioning
confidence: 99%